CURRENT STATUS OF RESEARCH ON THE STEM BLEEDING DISEASE OF COCONUT IN INDIA - KKN NAMBIAR; ROHINI IYER (International Coconut Community, 1991)
Stem bleeding disease of coconut was reported from India in 1922 by Sundaraman. Earlier Petch (1906) had reported the disease from Sri Lanka. Now the disease is known to occur in many coconut growing countries (Ohler, 1984).